Effects of biodiversity on the functioning of trophic groups and ecosystems - Cardinale, Bradley J.; Srivastava, Diane S.; Emmett Duffy, J.; Wright, Justin P.; Downing, Amy L.; Sankaran, Mahesh; Jouseau, Claire (Nature, 2006)
Species loss and productivity The question of whether species extinction alters the productivity of communities and ecosystem function is the subject of heated controversy. Work performed in the 1990s suggested that species loss can reduce productivity of communities and their efficiency in capturing and consuming limited resources. The interpretation of these studies was disputed, and subsequent work produced counter-examples that question the generality of biodiversity effects. Now Cardinale et al . report a meta-analysis of experimental studies of species diversity and ecological function. They conclude that species loss does impair ecological functioning, but that the magnitude of the effect depends on which species are actually lost. A meta-analysis of experimental studies addresses the relationship between species diversity and ecological functioning, and concludes that reduction in species loss does affect ecological functioning, but that the magnitude of these effects depends on which species are actually lost. Over the past decade, accelerating rates of species extinction have prompted an increasing number of studies to reduce species diversity experimentally and examine how this alters the efficiency by which communities capture resources and convert those into biomass 1 , 2 . So far, the generality of patterns and processes observed in individual studies have been the subjects of considerable debate 3 , 4 , 5 , 6 , 7 . Here we present a formal meta-analysis of studies that have experimentally manipulated species diversity to examine how it affects the functioning of numerous trophic groups in multiple types of ecosystem. We show that the average effect of decreasing species richness is to decrease the abundance or biomass of the focal trophic group, leading to less complete depletion of resources used by that group. At the same time, analyses reveal that the standing stock of, and resource depletion by, the most species-rich polyculture tends to be no different from that of the single most productive species used in an experiment. Of the known mechanisms that might explain these trends, results are most consistent with what is called the ‘sampling effect’, which occurs when diverse communities are more likely to contain and become dominated by the most productive species. Whether this mechanism is widespread in natural communities is currently controversial. Patterns we report are remarkably consistent for four different trophic groups (producers, herbivores, detritivores and predators) and two major ecosystem types (aquatic and terrestrial). Collectively, our analyses suggest that the average species loss does indeed affect the functioning of a wide variety of organisms and ecosystems, but the magnitude of these effects is ultimately determined by the identity of species that are going extinct.